Presacral neuroendocrine tumors associated with the Currarino syndrome. Issue 5 (1st March 2021) - Scott, Aaron T.; Tessmann, Jonathon B.; Braun, Terry; Brown, Bartley; Breheny, Patrick J.; Darbro, Benjamin W.; Bellizzi, Andrew M.; Dillon, Joseph S.; O'Dorisio, Thomas M.; Alderson, Alice; Bennett, Bonita; Bernat, John A.; et al.
Abstract: Currarino syndrome (CS) is an autosomal dominant syndrome caused by mutations in MNX1 and characterized by anorectal abnormalities, partial sacral agenesis, and presacral masses. The presacral masses are typically benign; however, malignant degeneration can occur, and presacral neuroendocrine tumors (NETs) have been reported in six cases. We report three individuals from two families affected by CS in which multiple individuals developed presacral NETs. The first family, 491, had six members with features of CS, including two siblings who presented with presacral, Grade 2 NETs, one of which had metastasized to bone and lymph nodes. A germline c.874C>T (p.Arg292Trp) mutation was found in a highly conserved region of MNX1 in three affected members who underwent sequencing. A second somatic variant/deletion in MNX1 was not detected in either patient's tumor. In the second family, 342, the proband presented with an incidentally discovered presacral NET. The proband's father had previously undergone resection of a presacral NET, and so genetic testing was performed, which did not reveal an MNX1 mutation or copy number variants. The lack of a second, somatic mutation in the tumors from family 491 argues against MNX1 acting as a tumor suppressor, and the absence of a germline MNX1 mutation in family 342 suggests that other genetic and anatomic factors contribute to the development of presacral NETs. These cases highlight the variable presentation of CS, and the potential for malignancy in these patients.